2003
DOI: 10.1021/bi035698i
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Reductase from Desulfoarculus baarsii:  Identification of Protonation Steps in the Enzymatic Mechanism

Abstract: Superoxide reductase (SOR) is a metalloenzyme that catalyzes the reduction of O2*- to H2O2 and provides an antioxidant mechanism in some anaerobic and microaerophilic bacteria. Its active site contains an unusual mononuclear ferrous center (center II). Protonation processes are essential for the reaction catalyzed by SOR, since two protons are required for the formation of H2O2. We have investigated the acido-basic and pH dependence of the redox properties of the active site of SOR from Desulfoarculus baarsii,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
194
3
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(235 citation statements)
references
References 28 publications
37
194
3
1
Order By: Relevance
“…These results show that, in presence of a steady-state concentration of the physiological substrate of SOR, neelaredoxin was able to catalyze the reoxidation of dithionite-reduced rubredoxin, in good agreement with similar experiments performed with P. furiosus SOR [7]. When bovine SOD was added to the system, the rate of rubredoxin reoxidation remained unchanged, because SOD is unable to receive electrons from any component of the reaction system at rates able to outcompete with the catalytic reduction of superoxide (10 9 M À1 s À1 ) [6,16,17,18]. However, when SOD was added in place of SOR, reoxidation of rubredoxin was totally inhibited, which confirmed the superoxidemediated character of the observed electron transfer reaction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results show that, in presence of a steady-state concentration of the physiological substrate of SOR, neelaredoxin was able to catalyze the reoxidation of dithionite-reduced rubredoxin, in good agreement with similar experiments performed with P. furiosus SOR [7]. When bovine SOD was added to the system, the rate of rubredoxin reoxidation remained unchanged, because SOD is unable to receive electrons from any component of the reaction system at rates able to outcompete with the catalytic reduction of superoxide (10 9 M À1 s À1 ) [6,16,17,18]. However, when SOD was added in place of SOR, reoxidation of rubredoxin was totally inhibited, which confirmed the superoxidemediated character of the observed electron transfer reaction.…”
Section: Discussionsupporting
confidence: 82%
“…Only the reduced colorless ferrous form of the active site iron is able to react with superoxide, with a virtually diffusion controlled rate of 10 9 M À1 s À1 , leading to the formation of the blue ferric state of the enzyme, which suggests the existence of an electron donor to regenerate the ferrous active form and complete the catalytic cycle of the enzyme [6,16,17,18]. The in vivo electron donor to SOR has generally not been established but previous work has strongly suggested that a rubredoxin (Rd) could be the proximal electron donor to superoxide reductases during periods of oxidative stress [7,8,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It displays a high redox potential of about + 300 mV (vs. NHE) at neutral pH and remains mainly in a reduced form in the presence of air [15][16][17][18]. Center II has an open coordination site, which represents the site where superoxide binds and is reduced by the ferrous iron to H 2 O 2 (eq.…”
Section: Introductionmentioning
confidence: 99%
“…Center II has an open coordination site, which represents the site where superoxide binds and is reduced by the ferrous iron to H 2 O 2 (eq. 2) [16][17][18][19][20][21] Two main classes of SORs have been described, associated with the presence of an additional N-terminal domain, which chelates an additional mononuclear iron center. When present, this iron center, named center I, is chelated by four cysteine residues in a distorted tetrahedral similar to arrangement of rubredoxin, in a fold very similar to that found for the small electron transfer protein desulforedoxin [22].…”
Section: Introductionmentioning
confidence: 99%
“…10 The reaction mechanism of SOR, involving transfer of an electron and two protons to superoxide to form hydrogen peroxide, has been studied in detail using kinetic and spectroscopic techniques. 12,13,14,15,16,17,18 Using kinetic data, Nivière et al and Kurtz et al have proposed the presence of at least one Fe III intermediate (henceforth referred to as intermediate I, characterized by a CT band at 600 nm) in the reaction. The formation of the intermediate was diffusion controlled and had no pH dependence or deuterium isotope effect and thus was proposed to be an Fe III -μ 2 -O 2 2− species.…”
Section: Introductionmentioning
confidence: 99%